STUDIES OF VIOLENCE IN COLOMBIA BEFORE VIOLENTOLOGY - Cartagena, Catalina (2015)
This article is analytically structured in two parts: The first, shortly presents an overview of violence in Colombia taking into account the history and development of the so-called violence during the first half of the twentieth century. The second part shows a before and after regarding the interpretations on violence in connection with the institutionalization of the social sciences in the country. Specifically, the aim of this article is to show how the institutionalization of the social sciences had a substantial impact on the construction of an academic space especially devoted to the subject of violence, which would then be recognized as violentology.